1998
DOI: 10.1159/000018003
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the Finn Chamber<sup>®</sup> Nickel Patch Test in Two Different Phases of the Ovulatory Menstrual Cycle

Abstract: Background: Studies on nickel patch test reactivity and reproducibility of positive tests at different points of the menstrual cycle are heterogeneous. Objective: To investigate if non-reproducibilities of positive nickel sulphate patch tests in the two different phases of ovulatory menstrual cycles with the endocrine evidence of luteal phase adequacy are statistically different. Methods: 15 women (group 1) with positive Finn chamber® nickel patch test results in the follicular phase of the ovulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Therefore, this effect can be observed even after a reasonable amount of time for recovery. Similarly, Friedmann et al also produced a lowered sensitization threshold to allergens administered by patch test on repeat exposure (55). However, the lack of a booster effect is evident in other studies (3,8,42).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, this effect can be observed even after a reasonable amount of time for recovery. Similarly, Friedmann et al also produced a lowered sensitization threshold to allergens administered by patch test on repeat exposure (55). However, the lack of a booster effect is evident in other studies (3,8,42).…”
Section: Discussionmentioning
confidence: 95%
“…After 6 weeks following the first test, testing was performed on the counter phases of the ovulatory cycle. They came to the conclusion that the nickel patch test results were not influenced by the phases of the ovulatory cycle in their study of 23 patients 5 …”
Section: Discussionmentioning
confidence: 99%
“…They came to the conclusion that the nickel patch test results were not influenced by the phases of the ovulatory cycle in their study of 23 patients. 5 In their study of 29 women whom they challenged with sodium laurate sulfate as an irritant patch test at day 1 and at days 9 through 11 of the menstrual cycle, Agner and colleagues have shown that there were differences in the reactivity of female skin with phases of the cycle, finding the strongest reaction to the patch test against sodium lauryl sulfate during days 9-11, which corresponds to the period when the highest estrogen levels are observed. 3 Alexander has pointed out to the differences of patch testing throughout the menstrual period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations